Analysis of Sea Surface Temperature (SST) Patterns in Arafura Waters Using Google Earth Engine (GEE) for Early Detection of Environmental Threats - Sadewa, Annisa Harum; Harsono, Gentio; Prihanto, Yosef; Haloho, Luwis Surani (Formosa Journal of Science and Technology, 2024)
Global warming that is happening today can result in an increase in sea surface temperatures. High sea surface temperatures can potentially disrupt the stability of ecosystems in Arafuru Waters. The waters of Arafuru are located in the south of Papua and border the country of Australia. This study aims to analyze the increase in sea surface temperature in waters using a satellite image processing method with Google Earth Engine (gee) software in a span of one year in 2021. The results obtained in this study are that the sea surface temperature value is around 28-300C which is in the medium category according to the Ministry of Marine Affairs and Fisheries. In this study, it is expected to be able to deal with environmental threats caused by rising sea surface temperatures, especially marine life.